Health education. Nurses’ experiences with the family health strategy - Roecker, Simone; Marcon, Sonia Silva (Investigación y Educación en Enfermería, 2025)
Objective. To describe nurses’ who participate in the Family Health Strategy (FHS) educational practice. Methodology. Qualitative study, carried out in 2010. Semi-structured interviews about daily experiences of 20 nurses who worked with the FHS in the 10th Health Regional of Paraná, Brazil, were done. Results. All the nurses confer great importance to health education, which they do daily. At the individual level, childcare guidance is highlighted, while in the group level, group educational activities – pregnant women, hypertensive patients, and smokers- were the most frequent ones. In some stories it was appreciated that the evaluation of educational necessities of the population was done without the effective participation of the community. Conclusion. FHS practice should be reoriented to health’s promotion and prevention, trying to get family and general community active participation, strengthening new formulas about thinking and doing in health.